1983
DOI: 10.1016/0014-5793(83)80612-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical evidence for the presence of 5mC, 6mA and 7mG in human, Drosophila and mealybug DNA

Abstract: We have reported that production and characterization of antibodies highly specific to 5-methyl-cytosine (SmC) and the development of a sensitive immunochemicai method for the detection of 5mC in DNA [EBBS Lett. (1982) 150, 4691. Extension of this method to two other modified bases, 6-m~hyladenine (6mA) and %methyiguanine (7mG), is reported here. By use of this immunochemical approach, we are able to detect 5mC, 6mA and 7mG in human and Drosophila DNA and confirm their presence in the DNA of two mealybug spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…) reported were high amounts of 6-methyladenosine and 7-methylguanosine which are rarely found in DNA of higher eukaryotes. This was later confi rmed in the same species by Achwal et al (1983) using a highly sensitive immunochemical approach. Devajyothi and Brahmachari (1992) reported a CpA methylase from the mealybug Planococcus lilacinus which could methylate both (CpG) and (CpA) dinucleotides.…”
Section: Models For Imprinting In Mealybugsmentioning
confidence: 99%
“…) reported were high amounts of 6-methyladenosine and 7-methylguanosine which are rarely found in DNA of higher eukaryotes. This was later confi rmed in the same species by Achwal et al (1983) using a highly sensitive immunochemical approach. Devajyothi and Brahmachari (1992) reported a CpA methylase from the mealybug Planococcus lilacinus which could methylate both (CpG) and (CpA) dinucleotides.…”
Section: Models For Imprinting In Mealybugsmentioning
confidence: 99%
“…The presence of unusual methylation like 6mA, 7mG and 5mC and non-CpG methylation was reported in P. lilacinus [Deobagkar et al, 1982;Achwal et al, 1983]. Hypermethylation of genomic DNA in males in Pseudococcus obscurus and Pseudococcus calceolariae was reported by Scarbrough et al [1984] and enrichment of CpG methylation in males of P. lilacinus was demonstrated by Mohan et al [2005], while Bongiorni et al [1999] found hypomethylation in the paternal set in P. citri .…”
mentioning
confidence: 92%
“…The method as described 47,48 was used for detection of 5-methylcytosine (5-mC). MRC5 genomic DNA (500 ng) was spotted on nitrocellulose membrane (Schleicher & Schuell), dried and cross-linked by exposure to ultraviolet on both sides of the membrane for 3 minutes.…”
Section: Immunochemical Staining For the Detection Of 5-methylcytosinementioning
confidence: 99%